Psoralea corylifolia L. Attenuates Nonalcoholic Steatohepatitis in Juvenile Mouse - Zhou, Lishan; Tang, Jianqiao; Xiong, Xiaoli; Dong, Hui; Huang, Juan; Zhou, Shunchang; Zhang, Lingling; Qin, Huan; Yan, Suqi (Frontiers in Pharmacology, 2017)
Psoralea corylifolia L. (PC) is a traditional Chinese herb used to treat yang deficiency of the spleen and kidney in pediatric disease. Recent studies have shown its liver protection and anti-oxidative effects. The aim of this study was to explore the effect and mechanism of PC on nonalcoholic steatohepatitis in juvenile mice. The juvenile mouse model of nonalcoholic fatty liver disease/ nonalcoholic steatohepatitis (NAFLD/NASH) was established by being fed a high-fat diet in maternal-offspring manner. PC granules were prepared and the quality was assessed. The main components were identified by high performance liquid chromatography. Then, different dosages of PC were administered for 6 weeks. Homeostatic model assessment of insulin resistance, plasma liver enzymes, hepatic morphology, hepatic superoxide anion, and triglyceride/total cholesterol levels were examined. The changes of nuclear factor-κB (NF-κB) activity phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) and protein kinase C -α (PKC-α) /nicotinamide-adenine dinucleotide phosphate (NADPH) oxidase signaling pathways in hepatic tissues were also determined. Our data demonstrated that PC significantly improved liver dysfunction, liver triglyceride/total cholesterol accumulation and insulin resistance in juvenile NAFLD/NASH mice. PC also alleviated hepatic steatosis, inflammatory cell infiltration, and fibroplasia in the portal area. Additionally, PC inhibited the activation of NF-κB and the mRNA expression of inflammatory factors while enhancing PI3K/Akt signaling in hepatic tissues. PC could also reduce hepatic superoxide anion levels, and NADPH oxidase activity as well as p47phox protein expression and PKCα activation in hepatic tissues. The results suggest that PC is effective in the treatment of NASH in juvenile mice. The mechanism may be related to the attenuation of hepatic oxidative stress through the PKC-α/NADPH oxidase signaling pathway.